Survey of medical, dental and nursing services in centres for intellectually and physically disabled children in Cape Town and its environs - Westwood, Anthony Thomas Read (Department of Paediatrics and Child Health, 2017)
This study describes the present medical, dental and nursing services in and used by centres for intellectually and physically impaired children in Cape Town and its environs. The information was gained by means of a structured questionnaire. Thirty three of the 34 centres with a total of 3480 children are included. Twelve are Special Care Centres, 15 Training Centres and 6 are Special Schools. The number of children enrolled ranges from 9 to 400. At the time of the study 9 of the centres were for white children, 17 for coloured children, 5 for black children and 2 were multiracial. Nine of the 11 Special Care Centres were not government supported while only 6 of the other centres were mainly funded from non-government sources. Nurses employed at the centres had worked an average of 8 years at their centres, 23,5% of them having worked with disabled children prior to taking up their present posts. Of the Special Care Centres, only the two residential ones had a nurse on the staff. All the Special Schools had at least one nurse. 57,5% of the centres have a doctor or doctors visiting the centre. Two of the others have regular medical care for the children arranged with local health centres. All the Special Schools are visited while 25% of the Special Care Centres and 33% of the Training Centres receive medical visits. The number of doctors visiting a centre varies from 1 to 7. The doctors come from a variety of services both private and public. Most of the doctors do not receive remuneration for their services. Of the 1 7 centres who have no doctors visiting, the majority depend on parents to take their children to a medical facility if there are problems related to the child's disability. For 7 of them, there is no other option. A similar pattern exists for medical problems unrelated to the child's disability. Six centres make use of medical facilities as a first option in these circumstances. For emergencies only 1 centre can count on a doctor to come to the centre. Ten centres may be able to get a doctor to come. The General Hospitals are the most common facility used in an emergency. Dentists visit 4 of the centres. Twelve of the remaining 29 centres arrange regular dental visits for the children. Eleven of the 13 Special Care Centres do not have regular visits to a dentist arranged. Fifteen centres receive visits from Community Nurses and these are local authority nurses in the main. Their functions are limited in all but one case to contraception, immunisation, Heaf testing or genetic services. There are 10 centres which receive visits from neither doctor, dentist nor nurse (7 Special Care Centres, 3 Training Centres). 32% of the interviewees were satisfied with the services received. The most common improvement sought was to have a doctor visit the centre. Of those with a doctor visiting, 28% wanted the doctors to deal with intercurrent problems as well as the child's disability. The need for paramedical services was also expressed. Further detail is presented and the implications of the findings discussed.